Need Analysis of Dyslexia Students in English Reading Comprehension Instructions - Margaret Stevani; Karisma Erikson Tarigan (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2022)
The challenges of learning English as a foreign language presented issue for dyslexia students who had deficiencies in reading comprehension involving information processing, concentration, and sensory motor skills. The aims of this research were to describe the dyslexia students’ needs in English reading comprehension. The sample consisted of 117 dyslexia students aged 13-16 years old from Karya Murni Special Needs School and Ananda Karsa Mandiri School, North Sumatra, Indonesia. The data were in the form of descriptive qualitative research which was taken from interview, questionnaire, and test. The results of this research proved the analysis of: (1) the physical, emotional, and social characteristics of dyslexia students, (2) the characteristics of dyslexia students’ learning style and testing reading comprehension test, (3) the need analysis for dyslexia students in teaching method in the classroom, (4) the need analysis of dyslexia students in reading comprehension, (5) the factors why dyslexia students had difficulty in English as a foreign language, and (6) the factors why dyslexia students had difficulty in English reading comprehension. With needs analysis, it was expected the identification of necessities, lacks, and wants could be formulated properly as a basis to prepare English reading teaching materials.